FAKTOR-FAKTOR YANG MEMPENGARUHI MELEMAHNYA GOOD CORPORATE GOVERNANCE DI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2017-2019 - Ropidah Sopiani; Abdul Wahid Mahsuni; Junaidi Junaidi (Universitas Islam Malang, 2020)
ABSTRACTThis research was conducted to determine the factors that affect the weakening of good corporate governance in companies listed on the Indonesian stock exchange (BEI) in 2017-2019. In this study, 30 samples of companies listed on the Indonesian stock exchange (BEI) in 2017-2019 were taken. The analytical method used is multiple linear regression. Based on the results of the tests that have been carried out, it is concluded that simultaneously the variables of leverage, investment opportunities, and ownership concentration have a significant effect on the weakness of good corporate governance. The partial test results show that the leverage variable has a significant effect on weak good corporate governance, the investment opportunity variable has no significant effect on the weak implementation of good corporate governance, and the ownership concentration variable has a significant effect on weak good corporate governance. Keywords : Leverage, investment opportunities, ownership concentration